Inventaire et vulnérabilité territoriale des basses terres du Saint-Laurent (Québec, Canada) face au projet d’exploitation des gaz de schiste - Christiane Gagnon; Majella-J Gauthier (IdeAs)
In the framework of the Application plan of the Strategic Environmental Assessment on Shale Gas (Government of Quebec, 2011), 73 scientific studies were conducted between 2013 and 2014 to investigate social, economic and environmental issues. One of them, which was conducted by the authors of this article, was meant to produce an inventory of the territory covering all land uses in three Quebec administrative regions, concerned by possible shale gas exploitation. It answers two basic questions of all environmental assessments, namely: what is the initial state of the land used involved in this gas development project and what would be the impact of this industry on existing uses? This article summarizes the voluminous research report responding to a mandate from the Quebec government. It focuses on the methodology used and on the main outcomes of the study regarding the identification of sensitive areas, at a micro-regional level, and the regional territorial vulnerability. In conclusion, a number of applications for future planning and management of territory are identified.